PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, KOMPETENSI APARATUR DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN SRAGEN - Wibowo, Widya Lutfi; Suharno, Suharno; Widarno, Bambang (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study aims to analyze the effect of the application of government accounting standards, apparatus competence, and internal control systems on the quality of the financial statements of the Regional Government of Sragen Regency. In the study using survey methods conducted at BPKPD Sragen Regency, with data sources namely primary and secondary. Data collection techniques are observation and questionnaire. Sampling technique: purposive sampling technique with a total of 50 respondents. Data analysis techniques used descriptive analysis, instrument testing, classic assumption tests, multiple linear regression analysis, and hypothesis testing. The variables used are the application of government accounting standards, apparatus competence, and internal control systems as independent variables, and the quality of financial statements as the dependent variable. The results of the study are the application of government accounting standards, apparatus competence and internal control systems have a significant positive effect on the quality of financial reports in Sragen Regency.